A Feasibility Study on Using the Blockchain to Build a Credit Register for Individuals Who Do Not Have Access to Traditional Credit Scores - Ortlepp, Bryony (African Institute of Financial Markets and Risk Management, 2020)
In South Africa and many other countries, credit registers and credit scores are used to determine how much credit a person can get access to, as well as the interest rate which they will be charged. In addition to this, some companies (such as insurance companies and rental agencies), use this data as part of the process to vet potential clients before allowing them to sign a contract. Part of the problem with this approach is that only certain records are stored on these credit registers. This excludes a large number of individuals, specifically those who are unbanked, those who have not got access to credit from formal institutions or those who do not own property and therefore pay their landlord for utilities. The purpose of this research is to determine the feasibility of using blockchain to store payment histories from small businesses to give their clients access to a credit record. The case study for this research will look specifically at a business which offers insurance to individuals living in informal settlements. This could be extended to many other businesses who work within informal settlements which allow cash payments on a regular basis for services offered. Shops in informal marketplaces which allow people to take products on credit and only pay later could also be included. By storing these transactions on the blockchain, individuals who would not usually have access to a credit history will have access to records of transactions that they have made and will be able to use these to show their ability and willingness to meet their financial obligations. This paper provides insight into existing credit registers and the process followed to build an informal credit register on the blockchain. The research covers an investigation into the feasibility of the project and it was found that this could is feasible and could add a lot of value, especially to those who do not have a credit history. There are many considerations, such as speed, security and costs which need to be taken into account, but these are outweighed by the benefits of the blockchain.